Ibrutinib as initial therapy for elderly patients with chronic lymphocytic leukaemia or small lymphocytic lymphoma: an open-label, multicentre, phase 1b/2 trial - O’Brien, Susan (2013)
BACKGROUND: Chemoimmunotherapy has led to improved numbers of patients achieving disease response, and longer overall survival in young patients with chronic lymphocytic leukaemia; however, its application in elderly patients has been restricted by substantial myelosuppression and infection. We aimed to assess safety and activity of ibrutinib, an orally administered covalent inhibitor of Bruton tyrosine kinase (BTK), in treatment-naive patients aged 65 years and older with chronic lymphocytic leukaemia. METHODS: In our open-label phase 1b/2 trial, we enrolled previously untreated patients at clinical sites in the USA. Eligible patients were aged at least 65 years, and had symptomatic chronic lymphocytic leukaemia or small lymphocytic lymphoma requiring therapy. Patients received 28 day cycles of once-daily ibrutinib 420 mg or ibrutinib 840 mg. The 840 mg dose was discontinued after enrolment had begun because comparable activity of the doses has been shown. The primary endpoint was the safety of the dose-fixed regimen in terms of frequency and severity of adverse events for all patients who received treatment. This study is registered with ClinicalTrials.gov, number NCT01105247. FINDINGS: Between May 20, 2010, and Dec 18, 2012, we enrolled 29 patients with chronic lymphocytic leukaemia and two patients with small lymphocytic lymphoma. Median age was 71 years (range 65–84), and 23 (74%) patients were at least 70 years old. Toxicity was mainly of mild-to-moderate severity (grade 1–2). 21 (68%) patients had diarrhoea (grade 1 in 14 [45%] patients, grade 2 in three [10%] patients, and grade 3 in four [13%] patients). 15 (48%) patients developed nausea (grade 1 in 12 [39%] patients and grade 2 in three [10%] patients). Ten (32%) patients developed fatigue (grade 1 in five [16%] patients, grade 2 in four [13%] patients, and grade 3 in one [3%] patient). Three (10%) patients developed grade 3 infections, although no grade 4 or 5 infections occurred. One patient developed grade 3 neutropenia, and one developed grade 4 thrombocytopenia. After a median follow-up of 22·1 months (IQR 18·4–23·2), 22 (71%) of 31 patients achieved an objective response (95% CI 52·0–85·8); four patients (13%) had a complete response, one patient (3%) had a nodular partial response, and 17 (55%) patients had a partial response. INTERPRETATION: The safety and activity of ibrutinib in elderly, previously untreated patients with symptomatic chronic lymphocytic leukaemia, or small lymphocytic lymphoma is encouraging, and merits further investigation in phase 3 trials. FUNDING: Pharmacyclics, Leukemia and Lymphoma Society, D Warren Brown Foundation, Mr and Mrs Michael Thomas, Harry Mangurian Foundation, P50 CA140158 to Prof J C Byrd MD.